IMPLEMETASI STANDAR KELULUSAN AL QUR’AN LEMBAGA PENDIDIKAN QUR’AN KABUPATEN WONOSOBO PADA METODE QIROATI DAN IQRO’ - Farid, Nur; Nurngain, Alfan; El Syam, Robingun Suyud (Ta'dib (Jurnal Ilmiah Pendidikan dan Peradaban Islam), 2024)
This article attempts to reveal the implementation of the Al-Qur'an graduation standards of the Wonosobo Regency Al-Qur'an Education Institute using the Qiroati and Iqro' methods. This paper is the result of qualitative field research using questionnaires, interviews, documentation, and observation as data collection techniques, then analyzed and conclusions are drawn. The subject of this research is the BADKO LPQ of Wonosobo Regency, involving informants, administrators, heads of madin/TPQ, and several ustadz-ustadzah of Al-Qur'an Education Parks (TPQ/Madin). The object of this research is the Al-Qur'an graduation standards of Al-Qur'an Education Institutions. The research results concluded that the implementation of the passing standards between BADKO LPQ, Qiro'at and Iqro' is different even though the goals are the same, namely: examiners, test materials, assessment standards and exam implementation. All three standardize the reading of the Qur'an according to the rules of tajwid, and use it as a means to achieve student achievement that can support the teaching and learning process and can motivate students to be better. The passing standards for the Qur'an are obtained from the learning implementation stage using classical, individual, semi-classical methods; as well as the learning assessment stage from the evaluation test at the end of learning.